(3MdjI GdCHQGQ hTYGQ GdCNjGQ aj JdNjU GdOYhGJ hGdCPcGQs - (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s ((3YHO dGdg Hf eMeO Hf MSjf GdMejOi s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdbgGQ CeG HYO abO bGd Gddg GdYXje GdYRjR GdMcje (B" (3aGPcQhfi CPcQce (B" (3hbGd JYGdi heG NdbJ GdLf hGdEfS EdG djYHOhf s
(3BNQgG (B:s
(3hGdG MGOjK GdUMjMI hGjVGM ebGUOgG hHjGf fcJ ef Ydhe GdGSGfjO hObGFb Gdabg heYGedGJ GdbdhH Je s
(3ef JMHjS GdefUhQ HGddg SfI (B1012s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs